Vitamin D: Role in Autoimmune Disease: Vitamin D: Role in Autoimmune Disease - Indah Sapta Wardani (LPPM Universitas Mataram, 2023)
Vitamin D has been associated with regulation on bone metabolism. Recently, the extra skeletal effect of vitamin D has been researched. Increasing evidence demonstrated strong association between vitamin D and many biological process that regulate immune responses. Vitamin D deficiency is known to be related to the development of the autoimmune diseases. The discovery of the vitamin d receptor in multiple immune cell lineage supports vitamin D with a novel role in modulating immune function and its subsequent role in the development or prevention of autoimmune disease. Vitamin d Deficiency is related to development and severity of reumathoid arthritis (RA), Systemic Lupus Erythematosus (SLE), multiple sclerosis, Type 1 diabetes mellitus and inflammatory bowel disease. Normal level of vitamin D is required for immune function focus on therapeutic and prevention effect in autoimmune disease.